A tool for the design of clinical forms supporting end-user integration. - Duftschmid, Georg (Medical informatics and the intrenet in medicine :an international journal of information processing in health care.)
Computer-based forms are a common input medium for recording medical data by the electronic mode. Efficient documentation requires that the forms satisfy the specific needs and habits of clinical end-users in the collectino of data. This can be effectively achieved by integrating the clinician in the process of designing the forms. However, most development environments used for the implementation of clinical forms are customized for computer specialists and are too technical in nature to be used by clinicians. We present a tool for the development of clinical forms, which supports the integration of end-users in the design process of the forms. The tool is customized for users from the medical domain, allowing interactive and intuitive development of forms based on the configuration of predefined components instead of programming. Clinicians may even design highly functional, complex forms autonomously without having to involve computer specialists at all. All collected data are stored on the basis of a generic data model favouring data retrieval. The described application has been successfully used at the University of Vienna and Graz medical schools since 1997 and 1999, respectively.